2021
DOI: 10.11121/ijocta.01.2021.00990
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi’s method of optimization of fracture toughness parameters of Al-SiCp composite using compact tension specimens

Abstract: The objective of this work is to investigate the process parameters which influence the fracture toughness of aluminum-silicon carbide particulate composite prepared using the stir casting technique. The Taguchi’s design of experiments is conducted to analyze the process parameters. Three parameters considered are composition of material, grain size and a/W ratio. From the Taguchi’s analysis, on compact tension specimens, aluminum 6061 reinforced with 9 wt% of the silicon carbide particles composite and a/W ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…1 and 2 shows that an increase in the FP, FT, and UP results in an increase in the tensile strength which can be also seen in As a result, except for case 5, the tensile strength estimated by the experimental and regression models agree with one another, with an error rate of less than 10 percent. Hence the validation of experimental and statistical results, agree with each other and are within the permissible error [20].…”
Section: Confirmation Experimentssupporting
confidence: 80%
See 1 more Smart Citation
“…1 and 2 shows that an increase in the FP, FT, and UP results in an increase in the tensile strength which can be also seen in As a result, except for case 5, the tensile strength estimated by the experimental and regression models agree with one another, with an error rate of less than 10 percent. Hence the validation of experimental and statistical results, agree with each other and are within the permissible error [20].…”
Section: Confirmation Experimentssupporting
confidence: 80%
“…Ajith et al [18] studied the FW of the S32205 duplex stainless steel and concluded the upset and FP were the majorly influencing process parameters. Many authors [19][20][21][22] used Taguchi's method of optimization and design of experiments (DOE) [23] to study the effect of process parameters. Literatures shows the dissimilar metals like aluminum-steel, steel-copper alloys, carbon-stainless steel, carbon steelaluminium are welded using the friction welding [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus to analyze the effect of each parameter on the fracture toughness, it is required to use the ANOVA [20]. The input function for the analysis of variance is experimental fracture toughness values.…”
Section: Resultsmentioning
confidence: 99%
“…These experimental data are then analysed to develop empirical models describing the relationships between material properties, specific factors, and their levels [176]. Many authors [23,24,183] developed equations for predicting fracture behaviour using regression methods, a type of empirical modelling technique that involves fitting mathematical models to the experimental data to describe the relationships between corrosive environment variables.…”
Section: Modelling and Predictive Approachesmentioning
confidence: 99%